The Effect of Perceptions of Price, Promotion, and Location on Purchasing Decisions at State Printing Lawso - Ervianti Nur Fatimah; Jamalaudin Khalid (Formosa Journal of Applied Sciences, 2023)
This study aims to examine the effect of price, promotion, and location perceptions on purchasing decisions at Lawson State Printing. This study used a survey-based quantitative research design using a purposive sample of 100 respondents. This study uses primary data or data collected directly from respondents which include price perception, promotion, and location on purchasing decisions. Based on research results. Price perception has a significant effect on purchasing decisions, promotions have a positive and significant effect, and location at Lawson Printing State also has a significant effect on purchasing decisions. Finally, the combined findings show that Perceived Price, Promotion, and Location together produce a significant effect on Purchase Decisions in Lawson State Printing.